SOSIALISASI ASESMEN PENDIDIKAN ANAK BERKESULITAN BELAJAR BAGI GURU SD NEGERI 02 CODO KABUPATEN MALANG - Hengky Triwijaya; Ruth Rosalia Nababan (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2022)
The general objectives of carrying out socialization regarding the educational assessment of children with learning difficulties are to: (a) increase teachers' understanding in assessing children with learning difficulties; (b) increasing teacher understanding in following up when finding children with learning difficulties. The socialization program regarding the educational assessment of children with learning difficulties at SD Negeri 02 Codo, Codo Village, Wajak District, Malang Regency is expected to increase understanding in assessing children with learning difficulties and its follow-up. The implementation mechanism in the outreach program regarding the educational assessment of children with learning difficulties starts with planning and ending with evaluation. The results of the implementation of socialization programs/activities regarding educational assessment of children with learning difficulties and assistance to teachers at CodoII Public Elementary School, Wajak District, Malang Regency were very satisfying because 100% of the expected results had been achieved.